Three new species of Grylloblatta Walker (Insecta: Grylloblattodea: Grylloblattidae), from southern Oregon and northern California - Schoville, Sean D. (Zootaxa, 2012)
Grylloblatta oregonensis new species, Grylloblatta siskiyouensis new species, and Grylloblatta marmoreus new speciesare described from the Klamath Mountains region of Oregon and California, U.S.A. Two species were found at OregonCaves National Monument, with G. oregonensis inhabiting the dark zone of caves and G. siskiyouensis inhabiting surfacehabitat and the twilight zone of caves. The third species, G. marmoreus, is known from Big Foot Cave and Planetary DairyCave, Marble Mountains, California. These three species are recognized on the basis of morphological characters anddistinguished from nearby Grylloblatta species. Analysis of genetic data from the cytochrome oxidase subunit II genesupports the morphological diagnosis of these three species as unique lineages and confirms their genetic divergence from other ice-crawler populations found in Oregon and California.